Bisalbuminemia: A Pathologist’s Insight of an Uncommon Phenomenon - Kapatia, Gargi; Wadhwa, Monika; Malhotra, Pankaj; Prakash, Gaurav; Aggarwal, Ritu (Journal of Laboratory Physicians, 2021)
Background The incidence of a bifid electrophoretic pattern in the albumin region on serum protein electrophoresis is an infrequent phenomenon. The availability of literature from India is scarce and is limited to case reports.Objective The aim of the study is to analyze the frequency of bisalbuminemia in an Indian referral facility. The study delved into their clinical associations.Material and Methods The retrospective case records of the patient from the departmental database were scrutinized. The study subjects were for an 8-year study period.Results There were about 39,900 serum electrophoresis performed in an 8-year study period. A total of 40 cases of bisalbuminemia were detected. The incidence in our cohort was 0.01%.Conclusion Bisalbuminemia, an overtly benign condition, is infrequent in Indian population although not rare. It is associated with several clinical disorders; however, the association seems to be plausibly coincidental.
Keywords: gel electrophoresis; albumin; serum protein electrophoresis